Mesenchymal stromal cells support endothelial cell interactions in an intramuscular islet transplantation model. Issue 1 (December 2015) - Fransson, Moa; Brännström, Johan; Duprez, Ida; Essand, Magnus; Le Blanc, Katarina; Korsgren, Olle; Magnusson, Peetra
Abstract Background Mesenchymal stromal cells (MSC) have been under investigation for a number of therapies and have lately been in focus as immunosuppressive actors in the field of transplantation. Herein we have extended our previously publishedin vitro model of MSC-islets in an experimental setting of islet transplantation to the abdominal muscle. Human islets coated with luciferase-GFP transduced human MSC were transplanted to the abdomen muscle tissue of NOD-scid ILR2γnull mice and cellular interactions were investigated by confocal microscopy. Results The MSC reduced fibrotic encapsulation and facilitated endothelial cell interactions. In particular, we show a decreased fraction of αSMA expressing fibrotic tissue surrounding the graft in presence of MSC-islets compared to islets solely distributed into the muscle tissue. Also, in the presence of MSC, human islet endothelial cells migrated from the center of the graft out into the surrounding tissue forming chimeric blood vessels with recipient endothelial cells. Further, in the graft periphery, MSC were seen interacting with infiltrating macrophages. Conclusions Here, in our experimentalin vivo model of composite human islets and luciferase-GFP-transduced human MSC, we enable the visualization of close interactions between the MSC and the surrounding tissue. In this model of transplantation the MSC contribute to reduced fibrosis and increased islet endothelial cell migration. Furthermore, the MSC interact with the recipient vasculature and infiltrating macrophages.